7th international work, global crisis and health seminar (2012)
The 7th International Work, Global Crisis and Health Seminar was held in Bogotá from the 19th to the 23rd of October 2009; it was coordinated by the Interfaculty Public Health PhD program and its objective was to create a space for debate about the worldwide crisis’ implications for health in the world of work and the challenges for public health arising from this. Regional leaders in health and safetyat work from Argentina, Brazil, México, Peru, Uruguay and Venezuela as well as leading national experts from the academic world and diverse entities attended the seminar. Workers’ representatives also participated most usefully in this academic event. The material included here has been organized into two parts. The first deals with the papers which were presented at the event, different approaches and methodologies having been adopted re investigation or advances concerning topics related to health and working conditions in Colombia. There is also a social-laborbased characterization of unemployed workers in the city of Medellín, discussing this population’s situation regarding their lack of health (insurance) protection, in terms of how public policy acts. There is a historical account of the Instituto Materno Infantil’s transformation through its workers’ experience and another study is focused on women working in Bogotá’s informal economy, characterizing the diseases and accidents related to such type of work. The second part consists of a series of reflection essays dealing with varied topics, all converging on problems regarding the world of work in times of global crisis and their effect on contemporary society. Such reflections touch on topics ranging from inequality in workers’ current situation (immersed in a risk society in a globalised world) to alternatives for future thinking about working conditions in the midst of crisis. Such reflection has involved informality, unemployment and underemployment as a question falling to several of society’s agents, where public health still has much to say. Discussion concerns topics such as voluntary abortion in migrant women, skills-based educational training and its relationship with the world of work, the manifestation of violence in organizations, the transformation of work in a new model of world accumulation having its impact on Colombia and the manifestation of emergent health–sickness negatives involved in the transformation of work and its crisis. Events which have happened since the 7th international seminar was held seem to suggest that the crisis has not yet been resolved, meaning that the reflections presented during the 7th international seminar have now become more important. The Universidad Nacional de Colombia ratifies its interest and commitment to contributing towards the search for alternatives for facing problems regarding health which are involved in the world of work.